(untitled) (Altre Modernità, 2010)
Adalgisa Giorgio (ed.), Writing Mothers & Daughters. Renegotiating the Mother in Western Narratives by Women (New York & Oxford: Berghahn Books, 2002, pp.258 ISBN1-57181-341-1) di Nicoletta Vallorani